2020
DOI: 10.1038/s41467-020-15607-z
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin architecture reorganization in murine somatic cell nuclear transfer embryos

Abstract: The oocyte cytoplasm can reprogram the somatic cell nucleus into a totipotent state, but with low efficiency. The spatiotemporal chromatin organization of somatic cell nuclear transfer (SCNT) embryos remains elusive. Here, we examine higher order chromatin structures of mouse SCNT embryos using a low-input Hi-C method. We find that donor cell chromatin transforms to the metaphase state rapidly after SCNT along with the dissolution of typical 3D chromatin structure. Intriguingly, the genome undergoes a mitotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 71 publications
4
60
0
Order By: Relevance
“…Such relaxed chromatin in early embryos is also conserved among fly, human ( Chen et al., 2019a ; Hug et al., 2017 ), and fish ( Nakamura et al., 2018 ; Kaaij et al., 2018 ). Similar relaxed chromatin organization was also found in SCNT mouse embryos, although at a slightly late stage (2-cell) ( Chen et al., 2020 ; Zhang et al., 2020 ). This extraordinary conservation during evolution raises a possibility that such relaxed chromatin states may very likely have important functions.…”
Section: Main Textsupporting
confidence: 74%
“…Such relaxed chromatin in early embryos is also conserved among fly, human ( Chen et al., 2019a ; Hug et al., 2017 ), and fish ( Nakamura et al., 2018 ; Kaaij et al., 2018 ). Similar relaxed chromatin organization was also found in SCNT mouse embryos, although at a slightly late stage (2-cell) ( Chen et al., 2020 ; Zhang et al., 2020 ). This extraordinary conservation during evolution raises a possibility that such relaxed chromatin states may very likely have important functions.…”
Section: Main Textsupporting
confidence: 74%
“…Moreover, a recent study by our group revealed spatiotemporally dynamic chromatin reorganization in SCNT embryos (Chen et al, 2020 ). Both aberrant TADs and compartment A/B organization are observed throughout early SCNT embryo development.…”
Section: Chromatin Remodelingmentioning
confidence: 88%
“…Moreover, overexpression of KDM4A also drastically increased the blastocyst rate of human SCNT and improves the derivation of human ntESC, with the similar mechanism as in mice (Chung et al, 2015 ). Our recent study also shows that H3K9me3 in donor cells also prevent the removal of topologically associated domains (TADs) during SCNT (Chen et al, 2020 ). These findings suggest that some H3K9me3, mainly associated with heterochromatin, is resistant to the cell conversion methods and presents as a barrier to reprogramming to pluripotency that impairs both the efficiency of reprogramming and the quality of embryogenesis.…”
Section: Histone Modificationsmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, vitamin c (Vc) induces demethylation of H3K9me3 by stimulating the activity of the histone demethylase Kdm3/4 and enhances the efficiency of somatic cell reprogramming (Wang et al , 2011). H3K9me3 is also a blockade in somatic cell nuclear transfer (SCNT) mediated reprogramming (Jullien et al , 2010; Matoba et al , 2014), indeed, injection of H3K9me3 demethylase Kdm4 mRNA into enucleated oocytes could greatly improve SCNT efficiency (Matoba et al , 2014; Chung et al , 2015; Liu et al , 2016; Liu et al , 2018; Chen et al , 2020b). Those results suggest that H3K9me3 is associated with closed chromatin to maintain cell identity, thus being an obstacle for somatic reprogramming.…”
Section: Introductionmentioning
confidence: 99%